Uma morte muito aperreada: Memória e esquecimento nas narrativas sobre um cangaceiro de Lampião em Mossoró - Falcão, Marcílio Lima (2011)
An agonizing death: Memory and forgetting about the narratives of a bandit of Lampião in Mossoró is a research that aims to study the history of construction of memories on the santification of the bandit Jararaca, dead on the night of june 19, 1927 in the cemetry São Sebastião in Mossoró by the police force that was scorting him for Natal, capital of Rio Grande do Norte. The interpretation is accomplished through analysis of documentation from the newspapers O Mossoroense, O Nordeste and O Correio do Povo, the analysis of works with narratives about the death of Jararaca, the importance of places of memory as spaces of conflict and statements of the devotees visiting the grave of Jararaca on Memorial day. We seek to understand the forms of movement, confiscation and reframing of memories about the santification of Jararaca.